Functional Impairment in Peripheral Artery Disease and How to Improve It in 2013 - McDermott, Mary McGrae (2013)
Lower extremity peripheral artery disease (PAD) affects eight million men and women in the United States and will be increasingly common as the U.S. population lives longer with chronic disease. People with PAD have poorer walking endurance, slower walking velocity, and poorer balance, compared to individuals without PAD. People with PAD may reduce their walking activity to avoid leg symptoms. Thus, clinicians should not equate stabilization or improvement in exertional leg symptoms with stabilization or improvement in walking performance in PAD. Additionally, even asymptomatic PAD patients have greater functional impairment and faster functional decline than individuals without PAD. Of the two FDA-approved medications for treating claudication symptoms, pentoxifylline may not be more efficacious than placebo, while cilostazol confers a modest improvement in treadmill walking performance. Supervised treadmill walking exercise is associated with substantial improvement in walking endurance, but many PAD patients do not have access to supervised exercise programs. Unsupervised walking exercise programs may be beneficial in PAD, but data are mixed.